MAKNA DIRI RESCUER PADA BADAN SEARCH AND RESCUE NASIONAL KANTOR SAR PEKANBARU - Yose Fratama; Genny Gustina Sari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Rescuer's work in every search and rescue operation is a high-risk job. Working as a Rescuer can endanger their own lives and require them in continuous preparedness. The high humanity and strong mental of Rescuer play a role in saving the lives of those whose bodies are incomplete. In their work, Rescuer always interacts well with fellow Rescuer as well as with the community in every search and rescue operation. This study aims to determine the meaning of Rescuer’s self and the meaning of humanity for Rescuer at National SAR Agency of Pekanbaru SAR Office.This research uses descriptive qualitative research type with phenomenology approach. Research subjects consist of four Rescuer at National SAR Agency of Pekanbaru SAR Office selected by using purposive technique. This study uses data collection techniques through in-depth interviews, observation, and documentation. To achieve the validity of the data in this study, researchers used extension of participation, triangulation, and reference adequacy.The results show that the first, the meaning given by the Rescuer at the National SAR Agency of Pekanbaru SAR Office to himself as a Rescuer that is as a humanity worker, helper in any case, and servant of the state. Second, the meaning of humanity for a Rescuer at the National Rescue Agency of Pekanbaru SAR Office in his work as Rescuer is helping others, as the basis of work, and the task of every human being.Keywords: Rescuer, Self meaning, Humanity